Atmospheric Aerosols Regional Characteristics - Chemistry and Physics - Abdul-Razzak, Hayder (IntechOpen, 2012)
The book is divided into two sections. The first section presents characterization of atmospheric aerosols and their impact on regional climate from East Asia to the Pacific. Ground-based, air-born, and satellite data were collected and analyzed. Detailed information about measurement techniques and atmospheric conditions were provided as well. In the second section, authors provide detailed information about the organic and inorganic constituents of atmospheric aerosols. They discuss the chemical and physical processes, temporal and spatial distribution, emissions, formation, and transportation of aerosol particles. In addition, new measurement techniques are introduced. This book hopes to serve as a useful resource to resolve some of the issues associated with the complex nature of the interaction between atmospheric aerosols and climatology.